Interaction study of binary solvent systems ionic liquid and deep eutectic solvent with rotenone - Zetty Shafiqa Othman,; Mamoru Koketsu,; Nurul Huda Abd Karim,; Saiful Irwan Zubairi,; Nur Hasyareeda Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
[BMIM]OTf and alcohol-based DES combination with a selected organic solvent (acetone and acetonitrile) have been proven to efficiently extracting rotenone (isoflavonoid biopesticide) compound compared to individual organic solvents. Their efficiency builds up interest to study the solvent-solute interaction that occurs between both selected solvent systems with rotenone. The interaction study was analyzed using FTIR, 1D-NMR and 2D- NMR (NOESY, HMBC). Correlation portrayed by NOESY and HMBC of [BMIM]OTf - standard rotenone mixture predicted probable hydrogen bonding between the oxygen of rotenone with acidic proton C2-H of [BMIM]OTf. While for the alcohol-based DES-rotenone mixture, the correlation shows probable interaction to occur between methyl and methoxy group rotenone with the hydroxyl group of 1,4-butanediol. In conclusion, potential hydrogen bonding that occurs between solvent and solute aid towards the solvent efficiency in extracting rotenone compound while emphasizing on the low cost and green mediated solvent systems.